Effect of heterocyclic capping groups on the self-assembly of a dipeptide hydrogel. Issue 10 (10th February 2016) - Martin, Adam D.; Wojciechowski, Jonathan P.; Warren, Holly; in het Panhuis, Marc; Thordarson, Pall
Abstract : In this work it is shown that the selection of heterocyclic capping group for a dipeptide hydrogel affects the self-assembly pathway taken, resulting in differences in mechanical strength, network structure and thixotropic properties. Abstract : The mechanism and design rules associated with the self-assembly of short peptides into hydrogels is currently not well understood. In this work, four diphenylalanine-based peptides have been synthesised, bearing heterocyclic capping groups which have different degrees of hydrogen bonding potential and nitrogen substitution. For these four peptides, zeta potential and electrical impedance spectroscopy measurements were undertaken to monitor gelation, with the impedance data showing different gelation times for each peptide hydrogel. Through a combination of atomic force microscopy and rheological measurmeents, including dynamic strain and frequency sweeps, and thixotropic tests, the relationship between the mechanism of self-assembly in these hydrogels and their macroscopic behaviour can be established. It is observed that the degree of nitrogen substitution affects the self-assembly mechanisms of the hydrogels and as such, that there is an interplay between branching and bundling self-assembly pathways that are responsible for the final properties of each hydrogel.